Perbedaan Rata-Rata Tekanan Darah Sistolik Pada Pasien Diabetes Melitus Tipe 2 Dengan Penyakit Jantung Koroner Dan Tanpa Penyakit Jantung Koroner Di Rsud Dr. Moewardi - Hidayat, Imam Lutfi, dr. Iin Novita Nurhidayati Mahmuda., M.Sc., Sp.PD (2017)
Peoples with diabetes mellitus with uncontrolled glucose levels had high risk to suffer coronary heart disease (CHD). The mechanism of the occurence of coronary heart disease in dabetes peoples is influenced by increase of the blood ressure. This study was to determined the difference in average of the systolic blood pressure in diabetes type 2 peoples with CHD and without CHD in Dr. Moewardi Hospital. This study was an observational analytic using cross sectional approach. Sampel was 50 diabetes peoples include 25 with CHD and 25 without CHD that were listed in the medical record office for periode September 2015 until September 2016 in Dr. Moewardi Hospital. The Statistical analysis was perform used non independent T test. Based on the analysis of data obtained that average of systolic blood pressure of type 2 diabetes mellitus peoples with CHD was 149,96 ± 15,686 and without CHD was 122,84 ± 15,217 with P value <0,001. There were a significant difference in average of systolic blood pressure in type 2 diabetes mellitus peoples with CHD and without CHD in the Dr. Moewardi Hospital.